Practical Insights to Design a Blockchain-Based Energy Trading Platform - Vahid Hosseinnezhad (IEEE, 2021)
Today, the development of decentralized energy management systems has accelerated due to the daily growth of renewable energy technologies and communications infrastructure. At the distribution system level, this approach has manifested itself with the emergence of the local energy market. In fact, the local energy market is becoming a new operating model to control local generation units. This paper describes the general architecture and elements used to implement a blockchain-based local energy market within a transactive management platform. After an overview of internet of things (IoT) communication technologies and the existing central-authority-based applications, the general structure and elements of peer-to-peer (P2P) networks are reviewed. Next, the concepts of blockchain-based technologies and the required specifications for different building layers are outlined based on the limited relevant literature available. The concepts and requirements are investigated to provide practical insights to design trading platforms.